Predicting successful "PER" reorganizations: Testing the applicability of Altman Z-Score on Portuguese companies - Carlos, Luís Miguel Gonçalves Oliveira Palma (2018)
The main objective of this dissertation is to test the applicability of Altman's bankruptcy prediction model of private companies in differentiating between companies that enter into “PER” and are successful in having an approved recovery plan and those that are unsuccessful. For this, the universe of companies that entered “PER” between May 2012 and December 2016 was collected, which translated into a viable sample of work consisting of 2,189 companies. The conclusions obtained allow us to state that when applied to the selected sample, the Altman model for private companies, in its initial formulation does not allow a proper distinction between the two groups of companies identified. Through the re-estimation of the Altman model, it was possible to obtain models that achieved results that were more positive. However, it is not possible to state that the model could robustly differentiate between companies with an approved plan and those without a plan approved without a significant error margin.